O modo de organização social como dimensão formativa da subjetividade - Spindola, Caroline dos Santos; Santos, Hugo Luiz Cardoso dos; Vieira, Maria Eduarda Trento (Universidade Federal de São Carlos, 2022)
Psychology, as a science that aims to understand and care for human anguish and suffering, created within the capitalist system, can get lost in its studies by not considering the totality of individuals and the social implications of the concrete determinants of life during its action and research. Traditional Psychology is understood as perspectives that individualize subjects and propose development as a result of internal processes to the individual. Differently, Critical Psychology understands that there is a dialectical relationship between the subject and the social environment. Based on these conceptions, the present work aims to analyze how some authors of Traditional Psychology (e. g., Neuropsychology, Winnicott, and Lacan) understand and postulate the influence of the mode of organization and social production in the process of construction of human subjectivity. From the reading of these authors and their commentators, we seek to find similarities and differences between these perspectives. This movement, made possible by the critical thinking of theoretical productions, is necessary given the academic training for the action and research of future professionals in the area. The professional activity, whatever it may be, needs to be mediated and crossed by social, cultural, and historical issues so that it is not alienating.
The mode of social organization as a formative dimension of subjectivity
Keywords: Subjetividade; Psicologia crítica; Psicologia tradicional; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO